Silencing of Syntaxin 1A in the Dopaminergic Neurons Decreases the Activity of the Dopamine Transporter and Prevents Amphetamine-Induced Behaviors in C. elegans - Lanzo, Ambra; Safratowich, Bryan D.; Kudumala, Sirisha R.; Gallotta, Ivan; Zampi, Giuseppina; Di Schiavi, Elia; Carvelli, Lucia (Frontiers in Physiology, 2018)
The dopamine transporter (DAT) is a cell membrane protein whose main function is to reuptake the dopamine released in the synaptic cleft back into the dopaminergic neurons. Previous studies suggested that the activity of DAT is regulated by allosteric proteins such as Syntaxin-1A and is altered by drugs of abuse such as amphetamine. Because C. elegans expresses both DAT (DAT-1) and Syntaxin-1A (UNC-64), we used this model system to investigate the functional and behavioral effects caused by lack of expression of unc-64 in cultured dopaminergic neurons and in living animals. Using an inheritable RNA silencing technique, we were able to knockdown unc-64 specifically in the dopaminergic neurons. This cell-specific knockdown approach avoids the pleiotropic phenotypes caused by knockout mutations of unc-64 and ensures the transmission of dopaminergic specific unc-64 silencing to the progeny. We found that, similarly to dat-1 knockouts and dat-1 silenced lines, animals with reduced unc-64 expression in the dopaminergic neurons did not respond to amphetamine treatment when tested for locomotor behaviors. Our in vitro data demonstrated that in neuronal cultures derived from animals silenced for unc-64, the dopamine uptake was reduced by 30% when compared to controls, and this reduction was similar to that measured in neurons isolated from animals silenced for dat-1 (40%). Moreover, reduced expression of unc-64 in the dopaminergic neurons significantly reduced the dopamine release elicited by amphetamine. Because in C. elegans DAT-1 is the only protein capable to reuptake dopamine, these data show that reduced expression of unc-64 in the dopaminergic neurons decreases the capability of DAT in re-accumulating synaptic dopamine. Moreover, these results demonstrate that decreased expression of unc-64 in the dopaminergic neurons abrogates the locomotor behavior induced by amphetamine. Taken together these data suggest that Syntaxin-1A plays an important role in both functional and behavioral effects caused by amphetamine.